Clinical and molecular characteristics associated with high PD-L1 expression in EGFR-mutated lung adenocarcinoma. - Jeremy Slomka; Hugo Berthou; Audrey Mansuet-Lupo; Hélène Blons; Elizabeth Fabre; Ivan Lerner; Bastien Rance; Marco Alifano; Jeanne Chapron; Gary Birsen; Laure Gibault; Jennifer Arrondeau; et al. (PLoS ONE)
Objective Recent evidence suggests that elevated levels of PD-L1 expression may be linked to early resistance to TKI and reduced survival in NSCLC with EGFR mutations. This study aimed to characterize the clinical and molecular features of EGFR-mutated lung adenocarcinomas and determine the prognostic significance associated with high PD-L1 expression. Materials and methods We conducted a retrospective chart review of 103 consecutive patients with advanced EGFR-mutated NSCLC, who received treatment between 01/01/2016 and 30/12/2020, at our institution. Results Among the tumors, 17% (n = 18) exhibited high PD-L1 expression (≥50% tumor proportion score), which was associated with a lower prevalence of common EGFR mutations (56% vs. 82%, p = 0.03) and a higher frequency of complex EGFR mutations (28% vs. 7%, p = 0.02). Univariate analysis did not reveal any significant differences in first-line response, progression-free survival, or overall survival between the PD-L1 ≥50% and <50% groups. However, multivariate analysis demonstrated that PD-L1 ≥50% was independently associated with shorter survival (HR = 2.57; 95%CI[1.20-5.55]; p = 0.02), along with male gender (HR = 2.77; 95%CI[1.54-4.19]; p<0.005), presence of liver metastases (HR = 5.80; 95%CI[2.86-11.75]; p<0.005) or brain metastases (HR = 1.99; 95%CI[1.13-3.52]; p = 0.02), and poor general condition at diagnosis (ECOG 3 and 4) (HR = 10.69; 95% CI[4.42-25.85]; p<0.005). Additionally, a trend towards a higher frequency of de novo resistance was observed in the PD-L1 >50% group (7% vs. 17%, p = 0.19). Conclusion High PD-L1 expression was more commonly found in lung adenocarcinomas with uncommon and complex EGFR mutations. Furthermore, high PD-L1 expression independently predicted poor survival. These findings warrant validation through prospective studies.